Diffuse descending necrotizing mediastinitis: surgical treatment and outcomes in a single-centre series - Janilionis, Ričardas; Jagelavičius, Žymantas; Petrik, Pavel; Kiškis, Gintaras; Jovaišas, Vytautas; Kybartas, Algis; Žilinskas, Arūnas; Liubertienė, Irena; Navickas, Giedrius; Valančius, Ramūnas (Acta medica Lituanica, 2013)
Objectives. Descending necrotizing mediastinitis is a severe infection spreading from the cervical region to the mediastinum. Since this pathology is uncommon, only a few reports of large series of patients with descending necrotizing mediastinitis have been published. The present aim was to evaluate our treatment strategy and survival for this disease by a retrospective chart review. Methods. Retrospective analysis of 45 cases with descending necrotizing mediastinitis was performed between 2002 and 2011. The mean age was 55.3 ± 15.4 years. The primary oropharyngeal infection was found in 16 (35.6%), an odontogenic abscess in 17 (37.7%) and other causes in 12 (26.7%) patients. Endo type I mediastinitis was assessed in 25 (56%) patients, Endo type IIA in 10 (22%) and Endo type IIB in 10 (22%) patients. Broad spectrum antibiotics were administered empirically and surgical treatment consisting of cervical drainage, thoracotomy with radical surgical debridement of the mediastinum and placement of permanent mediastinal irrigation were performed in all the cases. Results. Collar incision and drainage only were performed in 16 (35.6%) patients, whereas only transthoracic approach was used in five cases (11%). In the remaining 24 (53.4%) patients cervical drainage and thoracic operation were performed. Fifteen patients had severe complications: septic shock, multiple organ failure and haemorrhage from mediastinal vessels. The median hospital stay was 21  days. The outcome was favourable in 35 patients. Ten patients died (overall mortality 22.2%). There was a negative correlation between the time from the onset of symptoms till the first admittance to hospital and hospitalization time (Pearson correlation coefficient 0.357, p = 0.016). That allows us to suggest that time of illness spent at home without appropriate treatment plays a crucial role on the survival. It was found that younger age, Endo type I, negative bacterial culture and longer hospital stay are true precursors of favourable outcome. Conclusions. For descending necrotizing mediastinitis limited to the upper part of the mediastinum a transcervical approach and drainage may be sufficient. However, in advanced cases an immediate and more aggressive surgical approach is required to combat a much higher morbidity and mortality in this subset of patients.
Keywords: descending necrotizing mediastinitis; cervicotomy; thoracotomy; mediastinotomy; mediastinal irrigation